Sustainable agriculture: a perspective on fish culture for the small-scale resource-poor farmers of Bangladesh - Hoque, Muhammad Tafazzal (Taylor & Francis, 1995)
Fisheries play an important role in the agriculture-based economy of Bangladesh; inland water bodies comprise 12 percent of the total geographical area of the country. Still, the majority of the population is protein deficient. Per capita fish availability is 20.9 gm, which is only 26 percent of the standard nutrition level. More than 70 percejnt of the farmers are small and resource-poor and have no capacity to become involved in the semi-intensive and intensive fish culture, because most of the modern aquaculture practices are high-yielding but input costs are too high, not cost-effective, and involving higher risk.